Development Of The Robotization Process And It’s Impact On The Country’s Economy - et. al., Anna S. Shmoylova, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The paper highlights the basics and essence of innovation processes, describes ways to improve economic efficiency as a result of innovation, and highlights current problems that arise at the stages of innovation implementation. The main features of the robotization process, positive and negative consequences of its implementation are considered, and the impact of the robotization process on the development of the market economy is analyzed.